2001
DOI: 10.22358/jafs/67985/2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutritive value of new commercial linseed oily cultivars for ruminants

Abstract: The chemical composition, fatty acid profile, content of amino acids, minerals, and gross energy of seeds of some commercial linseed oily cultivars: brown-seed (Flanders, Opal and brown-seed mixture) and yellow-seed (Hungarian Gold, Linola™947, Linola™989, Hungarian ecotype) were determined. The nutritive value of seeds for ruminants was also assessed according to the Polish IZ-INRA (1997) standards. Lysine was the main limiting AA for all cultivars. There were significant differences between cultivars in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…The dietary fatty acid profile (not presented) differed, as linseeds of the regular HA cultivars Omega and Opal had a high content of α-linolenic acid, while linoleic acid predominated in the fatty acids of LA linseeds cv. Linola and LA oil, as well as in soya oil, which is in agreement with Borowiec et al (2001). Introducing LA linseed oil into the dietary formula decreased feed intake by 14%, soya oil decreased feed intake by 6% (P<0.05).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The dietary fatty acid profile (not presented) differed, as linseeds of the regular HA cultivars Omega and Opal had a high content of α-linolenic acid, while linoleic acid predominated in the fatty acids of LA linseeds cv. Linola and LA oil, as well as in soya oil, which is in agreement with Borowiec et al (2001). Introducing LA linseed oil into the dietary formula decreased feed intake by 14%, soya oil decreased feed intake by 6% (P<0.05).…”
Section: Resultssupporting
confidence: 84%
“…The decline might be connected with linseed lignans, mucilages or fatty acid profile (Van Elswyk, 1997). In recent years linseed cultivars containing oil low in α-linolenic acid and rich in linoleic acid have been introduced (Borowiec et al, 2001). Enrichment of laying hen diets with conjugated linoleic acid has been reported to decrease the yolk weight and cholesterol content of eggs (Szymczyk and Pisulewski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased content of C 18:1 and decreased content of C 18:3 were found in the seeds following higher nitrogen fertilization (P>0.05). Mean percentages of individual fatty acids, calculated irrespective of the compared cultivation factors, indicate a similar range of variations and are convergent with the findings of Borowiec et al (2001) or Froment et al (1998). Although the content of oleic acid slightly exceeded the values reported by Froment et al (1998).…”
Section: Resultssupporting
confidence: 87%
“…When added to animal rations, linseed may modify the fatty acid profile of their tissues (Barowicz, 1998). Borowiec et al (2001) showed that commercial varieties of linseed differ in the nutrient content as well as in the fatty acid profile of seeds. Both yellow-and brown-seeded cultivars have a similar fatty acids profile which is modified by agroclimatic conditions only to a small extent (Froment et al, 1998;Zając et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cultivars have a high content of C l83 , while the new cultivar Linola is higher in C 18 . 2 and lower in C |g3 acid (Borowiec et al, 2001). The aim of the present study was to determine the effects of dietary linseed cultivars (traditional ones and Linola) on performance as well as on the chemical composition of meat and liver of lambs.…”
Section: Introductionmentioning
confidence: 96%